Health Status of Elder People Living in Old Age Home of Kathmandu district, Nepal - Khadka, Kalpana; Karki, Tej Bahadur; Khanal, Lekhanath (Nepal Journal of Multidisciplinary Research, 2021)
Ageing is a process of gradual change in physical appearance and mental situation that causes a person to grow old. To be an old age is one natural process which cannot be controlled but to be alone in old age and need to take support of old age home is one social problem. The study aims to identify the health status of elder people living in the old age home of Kathmandu district. The study collected the data from 72 individuals, aged 60 years and above. The purposive sampling technique was used to select the respondents. The structured survey questionnaire was used for data collection. the result shows that in total majority (88.9%) of the elder people had some types of health problem. Basically, blood pressure, Gastric, and joint pain were the major health problem of elder people. Only 50% of the total respondents had visited the health post when they were ill. Statistically, there was no significant association between the male and female regarding their health problem because the p value was .182 which is greater than .05 significant level. Government should provide free health check-up facilities for such elder people living in the old age home.